2013
DOI: 10.4103/0970-9371.107517
|View full text |Cite
|
Sign up to set email alerts
|

Cytodiagnosis of alveolar soft part sarcoma: Report of two cases with special emphasis on the first orbital lesion diagnosed by aspiration cytology

Abstract: Alveolar soft part sarcoma (ASPS) is a rare neoplasm of uncertain cell of origin. Known to occur in adolescents and young adults, this tumor usually involves the muscles and deep soft tissues of the extremities and trunk. Orbital localization is rare and not yet subjected to cytological assessment, as per our literature search. We present here two cases of ASPS diagnosed by aspiration cytology, one in the orbit and the other in the lower extremity. The cells displayed abundant clear to finely vacuolated cytopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…2 On FNA biopsies, the smears show slight to moderate cellularity with some characteristic cytological features that includes: Many naked nuclei, scattered large, round to polygonal cells with prominent nucleoli and abundant granular and fragile cytoplasm. 3,4 Shabb et al found that numerous stripped tumor nuclei were a consistent cytomorphologic feature of ASPS cases and Wakely et al…”
Section: Discussionmentioning
confidence: 96%
“…2 On FNA biopsies, the smears show slight to moderate cellularity with some characteristic cytological features that includes: Many naked nuclei, scattered large, round to polygonal cells with prominent nucleoli and abundant granular and fragile cytoplasm. 3,4 Shabb et al found that numerous stripped tumor nuclei were a consistent cytomorphologic feature of ASPS cases and Wakely et al…”
Section: Discussionmentioning
confidence: 96%
“…4,5 Few cytology case reports and case series highlight the morphological features of ASPS. 1,6,7 ASPS cases also show intracytoplasmic rod-like crystalloids or inclusions, which are better highlighted on PAS-diastase staining. 4,7 However, after extensive screening, no definite crystalloids or inclusions could be found in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…Few cytology case reports and case series highlight the morphological features of ASPS 1,6,7 . ASPS cases also show intracytoplasmic rod‐like crystalloids or inclusions, which are better highlighted on PAS‐diastase staining 4,7 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations